A NEW CHARACTERIZATION OF SIMPLETIC GROUP S\(_8\)(2) - Yan, Yanxiong; Song, Naiqing; Feng, Yuming (Italian Journal of Pure and Applied Mathematics, 2014)
It is a well-known fact that characters of a finite group can give important information of the group’s structure. Also it was proved by Chen [1] that a finite simple group can be uniquely determined by its character table. In this paper, the authors attempt to investigate how to characterize a finite almost simple group by using less information of its character table, and successfully characterize the simpletic group S8(2) by its order and at most two irreducible character degrees of its character table.